2017
DOI: 10.1055/s-0043-106050
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products as Lead Compounds for Sodium Glucose Cotransporter (SGLT) Inhibitors

Abstract: Glucose homeostasis is maintained by antagonistic hormones such as insulin and glucagon as well as by regulation of glucose absorption, gluconeogenesis, biosynthesis and mobilization of glycogen, glucose consumption in all tissues and glomerular filtration, and reabsorption of glucose in the kidneys. Glucose enters or leaves cells mainly with the help of two membrane integrated transporters belonging either to the family of facilitative glucose transporters (GLUTs) or to the family of sodium glucose cotranspor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 74 publications
1
61
0
3
Order By: Relevance
“…Similarly, we have recently shown that EC did not modulate the protein levels of GLUT‐2 in hepatic cells . In addition, it should be mentioned that different natural products, including P and flavonoid enriched plant extracts, inhibit SGLT‐2, which contributed to reduce the glycemia . In this line, our results could suggest that EC and DHBA could contribute to decrease the glucose uptake by inhibiting SGLT‐2 without altering the expression of the glucose transporters, as described for dapagliflozin, empaglifozin, P, or other natural products …”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similarly, we have recently shown that EC did not modulate the protein levels of GLUT‐2 in hepatic cells . In addition, it should be mentioned that different natural products, including P and flavonoid enriched plant extracts, inhibit SGLT‐2, which contributed to reduce the glycemia . In this line, our results could suggest that EC and DHBA could contribute to decrease the glucose uptake by inhibiting SGLT‐2 without altering the expression of the glucose transporters, as described for dapagliflozin, empaglifozin, P, or other natural products …”
Section: Discussionsupporting
confidence: 78%
“…[33] In this line, our results could suggest that EC and DHBA could contribute to decrease the glucose uptake by inhibiting SGLT-2 without altering the expression of the glucose transporters, as described for dapagliflozin, empaglifozin, P, or other natural products. [3,28,33,34] Renal gluconeogenesis predominantly occurs in the proximal tubular cells. [2,4] Indeed, renal proximal tubular cells are particularly sensitive to the hyperglycemia because the glucose uptake is insulin-independent.…”
Section: Discussionmentioning
confidence: 57%
“…Of these, phlorizin, the first naturally occurring sodium glucose cotransport (SGLT) inhibitor, has been used to identify the SGLT mechanism (Vick, Diedrich, & Baumann, ). Following this, many natural product glucose transport inhibitors have been characterized, of which several compounds have been tested in vitro and in vivo, and in some cases have reached clinical trials as potential cancer chemotherapeutic agents (Blaschek, ; Choi, ; Granchi et al, ; Qian et al, ).…”
Section: Glucose Transport Inhibitors From Edible Plantsmentioning
confidence: 99%
“…In previous review articles, the overall information included on glucose transport and metabolism in cancer cells and the progress of new therapeutic developments for glucose transport inhibitors focused on small molecules, with only a limit number of natural products, were summarized (Qian et al, ). Natural product sodium glucose cotransporter (SGLT) inhibitors and their potential antidiabetic activity have been reviewed (Blaschek, ; Choi, ). In addition, synthetic and naturally derived glucose transport inhibitors and their potential anticancer activities have been discussed (Granchi et al, ; Granchi et al, ).…”
Section: Introduction and Significancementioning
confidence: 99%
“…These compounds not only control blood glucose but also have the potential to improve cardiovascular system function, reduce kidney disorders, and normalize the lipid profile (Fujita & Inagaki, ). Besides phlorizin, other natural product‐derived compounds have been investigated for their ability to reduce renal glucose reabsorption and improve glycemic control (Blaschek, ).…”
Section: Introductionmentioning
confidence: 99%